Winter leaf redness in mastic tree (Pistacia lentiscus L.) is associated with increased cellular damage levels and modified nitric oxide and hydrogen peroxide biosynthesis - Nikiforou, Constantinos; Filippou, Panagiota S.; Manetas, Yiannis; Fotopoulos, Vasileios (My University, 2014)
Recent evidence suggests that winter-red leaf phenotypes in the mastic tree (Pistacia lentiscus L.) are more vulnerable to chronic photoinhibition during the cold season, relative to winter-green phenotypes occurring in the same high light environment. The present study deals with the previously recorded induction of anthocyanins in leaves of winter populations of mastic tree, examining their correlation with cellular status and the potential coordinated involvement of reactive species networks. Red leaves with increased amounts of anthocyanins show higher concentrations of hydrogen peroxide (H2O2) and nitric oxide (NO). Furthermore, red leaves show higher extent of cellular damage manifested by increased lipid peroxidation and lower photosynthetic pigmentcontent compared with green leaves. The observed accumulation of reactive species is supported by increased activity of H2O2 (superoxide dismutase) and NO-producing (nitrate reductase) enzymes, respectively. Winter leaf redness may therefore be potentially used as a rapid phenotyping means to locate vulnerable mastic tree plants suffering from nitro-oxidative stress.
Keywords: Pistacia lentiscus L.; Anthocyanins; Nitric oxide; Hydrogen peroxide; Winter leaf reddening; Antioxidants